21st century education: Are We Heading the Right Direction of Improving Teaching and Learning as Needed by educational Programme - Yusup, Hashim (2014)
There are not much dialogues or discussions going on relating to 21 century learning in Malaysia. But we have several dialogues on e-learning or use of ICT in schools specifically the implementation of Smart Schools (1999) to prepare students for the information age, EduwebTV (2009) to provide education for all and recently the use of virtual learning using FrogAsia (VLE) as the platform to implement virtual learning in schools. At this juncture, I think some are not sure or at least inquisitive how these educational technology innovations fit into 21 century education or at least understand the concept that form the framework of 21 century learning. Is 21 century education part of the overall educational transformation envisioned by Malaysian government? If it is, this paper tries to look at some of the development that influence e-learning in schools and discuss whether we are going into the right direction of using instructional technology or educational technology to facilitate and improve teaching and learning. Some of the issues discussed are the concept and framework of 21 century learning, instructional and learning theories and new strategies in teaching and learning and educational technology standards that drive teachers, students and school administrators to implement e-learning in 21st century education.